Perspective on taxonomic classification of uncultivated viruses - Dutilh, Bas E; Varsani, Arvind; Tong, Yigang; Simmonds, Peter; Sabanadzovic, Sead; Rubino, Luisa; Roux, Simon; Muñoz, Alejandro Reyes; Lood, Cédric; Lefkowitz, Elliot J; Kuhn, Jens H; Krupovic, Mart; et al. (Current opinion in virology, 2021)
[Display omitted] Historically, virus taxonomy has been limited to describing viruses that were readily cultivated in the laboratory or emerging in natural biomes. Metagenomic analyses, single-particle sequencing, and database mining efforts have yielded new sequence data on an astounding number of previously unknown viruses. As metagenomes are relatively free of biases, these data provide an unprecedented insight into the vastness of the virosphere, but to properly value the extent of this diversity it is critical that the viruses are taxonomically classified. Inclusion of uncultivated viruses has already improved the process as well as the understanding of the taxa, viruses, and their evolutionary relationships. The continuous development and testing of computational tools will be required to maintain a dynamic virus taxonomy that can accommodate the new discoveries.